지방세포 신호와 소화기 질환 - 전훈재; Hoon Jai Chun; 금보라; Bo Ra Keum; 엄창섭; Chang Sub Uhm (The Korean journal of gastroenterology, 2006)
For the regulation of energy balance in various internal organs including gut, pancreas and liver, visceral adipose tissue and brain perform important sensing and signaling roles via neural and endocrine pathway. Among these, adipose tissue has been known as a simple energy-storing organ, which stores excess energy in triglyceride. However, it became apparent that adipocytes have various receptors related to energy homeostasis, and secrete adipocytokines by endocrine, paracrine and autocrine mechanisms. In this review, basic roles of adipocytes in energy homeostasis and the correlation between adipocyte signals and digestive diseases are discussed. (Korean J Gastroenterol 2006;48:67-74)